Early complicated schistosomiasis in a returning traveller: Key contribution of new molecular diagnostic methods. (February 2019) - Bonnefond, Simon; Cnops, Lieselotte; Duvignaud, Alexandre; Bottieau, Emmanuel; Pistone, Thierry; Clerinx, Jan; Malvy, Denis
Highlights: Serology and egg microscopy lack sensitivity for early schistosomal infection. Delayed diagnosis and treatment can lead to debilitating outcomes. PCR assay should be performed for the early detection of symptomatic schistosomiasis. Spinal cord schistosomiasis can appear very early after exposure. Early ectopic granuloma formation supports prompt antischistosome drug treatment without delay. Abstract: Early schistosomiasis poses a serious diagnostic challenge, because current standard diagnostic techniques based on serology and egg microscopy lack sensitivity at the initial presentation. We report spinal cord neuroschistosomiasis in a traveller developing 6 weeks after exposure. The diagnosis was confirmed by Schistosoma mansoni -targeted real-time PCR in blood and cerebrospinal fluid, before the results of conventional methods became positive. Molecular assays represent a paradigm shift for the difficult diagnosis of early schistosomiasis and related complications.